(untitled) - March, James J. (New York, 1994)
This book is a primer, a little compendium of idea for thinking about how decisions happen. It examines ideas of rational choice, particularly limited rationality; considers ideas of identity, appropriateness, and history-dependent rules; looks at multiple-person decision making, decisions made in the face of inconsistency in preferences or identities; treats the consequences for decision making of ambiguity in preferences, identities, and experience; finally, it considers the pospects for decision engineering
Keywords: Decision-making